A practical guide to energy management of facilities and utilities (ISmithers Rapra Pub., 2012)
Do you know how best to manage and reduce your energy consumption? This book gives comprehensive guidance on effective energy management for organisations in the polymer processing industry. This book is one of three which support the ENERGYWISE Plastics Project eLearning platform for European plastics processors to increase their knowledge and understanding of energy management.